Auctions vs negotiations in public procurement: Which works better? - Rafael Lalive; Armin Schmutzler (University of Zurich, Department of Economics, 2011)
Public agencies rely on two key modes to procure goods and services: auctions and direct negotiations. The relative advantages of these two modes are still imperfectly understood. This paper therefore studies public procurement of regional passenger railway services in Germany, where regional agencies can use auctions and negotiations to procure regional passenger rail services. This offers the unique opportunity to assess the two procurement modes within the same institutional and legal framework. We first characterize the decisions of the agency in a simple reduced form framework of negotiations and auctions. This analysis suggests accounting for the endogeneity of the choice of procurement mode by estimating the mode of procurement, quantity and price simultaneously. We then test this framework using information on lines that were auctioned and lines that were directly negotiated with the former monopolist. Results indicate (i) endogeneity of procurement choice can be fully characterized by observed line characteristics; (ii) frequency of service is 16 percent higher on lines that were auctioned compared to lines that were negotiated, and (iii) the procurement price is 25 percent lower on auctioned lines than on those with direct negotiations. Taken together, these results indicate a significant efficiency enhancing effect of auctions.
Keywords: D43; D44; R48; 330; auctions; negotiations; liberalization; passenger railways; public procurement; Öffentliche Dienstleistung; Schienenverkehr; Versorgungswirtschaft; Öffentlicher Auftrag; Auktionstheorie; Wohlfahrtsanalyse; Deutschland